TELAAH KONSEP ARSITEKTUR RUSTIC PADA BANGUNAN THE AHWAHNEE HOTEL - Tiara Amelia; Ari Widyati Purwantiasning (PURWARUPA Jurnal Arsitektur, 2022)
Rustic is an architectural concept that has a rustic feel and is a concept that emerged in the rural United States. Taking a rustic impression makes this concept dominant with natural elements and materials in the building, such as the use of wood, natural stone, exposed brick, and metal, while maintaining the rough shape of the material. Ahwahnee Hotel is an old historic building that has a rustic concept. The building is located in Yosemite National Park and is surrounded by forests and cliffs because, basically, rustic buildings exist in the open so they can blend in with the surrounding nature. This study uses a descriptive qualitative narrative method, where the research data is obtained from the study of literature. The purpose of this research is to understand the principles of rustic architecture, analyze hotel objects with rustic principles, and understand the application of rustic architecture in hotel buildings. Then there are conclusions to be obtained, namely a research result from the analysis of selected case studies with the application of rustic architectural principles in hotel buildings